On some univalence criteria for certain integral operators - DICU, Petrică; DICU, Mădălina; ALBIȘORU, Andrei-Florin (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
For analytic functions in the open unit disk, we define new general integral operators. The aim of this paper is to study these new operators and related univalence criteria. First of all, we recall some classes of functions defined on the unit disk. We will use functions from these classes to construct our integral operators. Secondly, we recall the univalence criteria that we use in the proofs of our results. Finally, we use the univalence criteria to establish univalence conditions related to our general integral operators. Mathematics Subject Classification (2010): 30C45. Received 19 March 2025; Accepted 07 October 2025.